Factors to Achieve Aesthetics in All-Ceramic Restorations - Ricardo Barao, Valentim Adelino [UNESP]; Gennari-Filho, Humberto [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pesqueira, Aldieris Alves [UNESP] (Lippincott Williams & Wilkins, 2010)
The demand for aesthetic restorations has increased during the last years. Dental ceramics are a successful alternative for some cases because of aesthetics and biocompatibility. Therefore, the aim of this literature review was to present the factors necessary to fabricate all-ceramic restorations with aesthetics similar to natural dentition. A search of English-language peer-review literature was completed using MEDLINE database from 1975 to 2009 including the keywords "aesthetic," "metal-free crown," "all-ceramic," and "color." It was observed that several factors influence aesthetics of all-ceramic restorations. Color scale, light source during color evaluation, characteristic of core material, color of supporting tooth, presence of root post, and type of cement are clinical factors that may influence color of the restorations. Laboratorial factors as technique for ceramic condensation, thickness, temperature, and number of firing cycles also influence the result of these crowns. Although several clinical and laboratorial factors influence aesthetics of all-ceramic restorations, the aesthetic success and longevity of these restorations depend on the integration with surrounding periodontal tissue.
Keywords: All-ceramic crowns; ceramic systems; aesthetic; color; shape; surface texture